Highbush blueberry proanthocyanidins alleviate Porphyromonas gingivalis-induced deleterious effects on oral mucosal cells. (October 2020) - Ben Lagha, Amel; Howell, Amy; Grenier, Daniel
Abstract: Strong evidence points to Porphyromonas gingivalis, a Gram-negative anaerobic bacterium, as a keystone species in the development of the chronic form of periodontitis. The aim of the present study was to investigate the ability of highbush blueberry proanthocyanidins (PACs) to alleviate the P. gingivalis -induced deleterious effects on oral mucosal cells. We first showed that highbush blueberry PACs protect the integrity of the gingival keratinocyte barrier against P. gingivalis -mediated damage, as determined by measuring the transepithelial electrical resistance and paracellular flux of FITC-conjugated dextran. Moreover, the PACs prevented the translocation of P. gingivalis across the gingival keratinocyte barrier model. The proteinase activity of P. gingivalis was inhibited by the PACs suggesting that they may exert beneficial effects by reducing proteolytic degradation of the epithelial tight junctions. Regulation of gingival fibroblast inflammatory reactions may be one of the ways to prevent and control periodontal disease progression and severity. We showed that PACs significantly reduce IL-6 and IL-8 secretion by P. gingivalis -stimulated gingival fibroblasts. The present study showed the capacity of highbush blueberry PACs to protect the integrity of an in vitro model of gingival keratinocyte barrier against P. gingivalis, and to attenuate the secretion of pro-inflammatory cytokines by gingival fibroblasts infected with P. gingivalis . These results suggest beneficial effects of blueberry PACs thus supporting the need for future clinical trials on the potential of these bioactive molecules for periodontal disease prevention and/or treatment. Highlights: Highbush blueberry PACs attenuate the deleterious effects of P. gingivalis on the gingival keratinocyte barrier. PACs prevent the translocation of P. gingivalis across the keratinocyte barrier. PACs inhibit the proteolytic activity of P. gingivalis . PACs attenuate the P. gingivalis -induced secretion of IL-6 and IL-8 by gingival fibroblasts.